STRATEGI PENGEMBANGAN KUALITAS KULINER ITIK PALEKKO DI RUMAH MAKAN KHAS BUGIS DI KABUPATEN SIDRAP - Fatmawaty, Fatmawaty; Nuddin, Andi; Halimah, Andi Sitti (Jurnal Pendidikan Teknologi Pertanian, 2019)
Business continuity that provides a home meal especially palekko menu can not be predicted so that business owners are required to develop appropriate strategies to develop the quality of the product in maintaining their business. This study aims to determine the strategy for developing the culinary quality of palekko ducks in Sidenreng Rappang Regency using SWOT analysis. The results of the matrix show the strategies that can be applied by the business owner is to open a business branch, promote, maintain and improve the quality of products, services, and HR by compiling a Standard Operating Procedure (SOP), working with suppliers with a work contract system to ensure availability of materials raw.